Răspunsuri

2014-11-10T15:39:06+02:00
Din A-B=956 rezulta ca A=956+B
                      apoi inlocuim in A+B=1010 rezulta B+956+B=1010
                                                                             2B+956=1010
                                                                             2B=54
                                                                             B=27 rezulta A=956+27
                                                                                                     =983
                                                                              C=983x42
                                                                                 =41286